Running economy of African and Caucasian distance runners - Weston, A. R.; Mbambo, Z.; Myburgh, K. H. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Anecdotal evidence suggests an advantageous physiological endowment of the African endurance athlete. Higher fractional utilization of O2max has been suggested but not measured directly, and investigations of running economy have been inconclusive. The aim of the current study was to measure a) running economy and b) fractional utilization of O2max, in African and Caucasian 10-km runners of similar body mass.